Influence of the Nature of Solvent on Extraction of Acetic Acid with Alamine 336 - Inci, Ismail (Asian Journal of Chemistry, 2010)
Studies have been made on the extraction of acetic acid by Alamine 336, a mixture of aliphatic tertiary amines, dissolved in various diluents. Diluents were chosen from different chemical classes—electron donating, electron accepting, polar and nonpolar—so as to examine the effects of diluent-complex interactions. These interactions were found to affect both the stoichiometry of reaction and the magnitudes of the corresponding equilibrium constants. As a result of batch extraction experiments distribution coefficients, loading factors and overall extraction constants were calculated. The results were interpreted by "acid-amine complex formation" approach, in which the stoichiometries of acid-amine complexes and corresponding equilibrium constants have been studied.